Система підготовки наукових і науково-педагогічних кадрів в Україні: ретроспектива розвитку і особливості формування - Демідова, Юлія Євгенівна; Тверитникова, Олена Євгенівна; Іліаш, Ніколає (Національний технічний університет "Харківський політехнічний інститут", 2019)
На основі залучення статистичних даних щорічних звітів політехнічних вишів України проведено аналіз започаткування та розвитку системи підготовки аспірантів у складі професійної освіти України впродовж ХХ ст. Висвітлено різні аспекти діяльності інституту аспірантури на тлі освітньої державної політики другої половини ХХ ст. та особливості розбудови аспірантури впродовж 1990–2000 рр. Акцентовано увагу на ролі професійного середовища вищої технічної школи в підготовці наукових кадрів. Досліджено чинники, що призвели до накопичення групи негативних рис у роботі аспірантури та атестації наукових кадрів. Визначено, що впродовж ХХ ст. аспірантура, як основна форма підготовки наукових кадрів постійно розвивалася й вдосконалювався, зокрема були запровадженні нові форми навчання: заочна, річна, цільова та залановано інститут здобувачів.

Problem setting. The study of issues related to the formation of the postgraduate training system in the vocational education system is a relevant task in terms of scientific personnel certification of higher technical schools. Recent research and publications analysis. Nowadays, many of Ukrainian and foreign scientist’s works are devoted to the study of issues of training highly qualified personnel. The authors emphasize the need to study the crisis phenomena of higher education in the 1980s to further development correction of modern educational trends. In the context of the new methodological approach, the issue of researching higher-education teaching personnel as one of the main components of the education system is considered. Attention is focused on the introduction of new alternative certification systems of scientific personnel based on European experience. Paper objective. To conduct a comparative analysis of Ukrainian experience in organizing professional training of highly qualified personnel during the 20th century, in particular, graduate students in the vocational education system. Paper main body. The training system for personnel in vocational education began to form in Ukraine in the first quarter of the 20th century. At that time, the first provisions for specialists training were developed, rules for admission to graduate school were proposed, the procedure for awarding degrees and planning recruitment for graduate school were determined. The provisions on training of scientific personnel were revised and normalized, the basic form of preparation of scientific potential, which consisted in writing and public defense of dissertation works was approved. Graduate study was considered to be completed if the thesis was defended. Gradually, postgraduate study became the main form of training for higher-level personnel. Despite the fact that the regimentation of postgraduate activities was positive, there were also disadvantages. What was important that the candidate had to defend a scientific work, and only then he was considered as a graduate of postgraduate study. A new stage in the development of the training of higher qualification personnel system began in the first postwar years. In order to activate and regulate the functioning of the training and certification of highly qualified personnel system during 1946-1949, numbers of resolutions were adopted. Also, a new form of study was created - a year-long postgraduate course. The further development of the postgraduate training system was filled with new reform measures, which helped to adjust some aspects of postgraduate study and to modernize the procedure for entry and postgraduate study. New requirements for improving the quality of the dissertation were proposed. In 1957, a new regulation on postgraduate study was developed. The main change was the possibility of graduation without a thesis defense. This had a negative impact on the number of defenses. At the beginning of the 1970's, the Institute of Graduate Studies of Ukraine, as the main form of training of scientific and scientific-pedagogical staff was practically formed. The defining trend of the 1990's was the expansion of the postgraduate network. The establishment of the Ministry of Education and the Higher Attestation Commission of Ukraine in early 1992, which began to perform centralizing functions in the training of higher qualification personnel system led to streamlining the activities of specialized scientific councils, expert councils of the Higher Attestation Committee of Ukraine and increased requirements for respondents. Conclusions of the research. Over the past century, the Institute of Postgraduate Professional Training for Scientific Staff had been continuously developing and improving. The characteristic features of the study period were looking for new, better forms of postgraduate training; expanding the list of specialties in the defense of scientific works; strengthening the requirements for the quality of dissertation research; improvement of the professional level of the teaching staff of universities and research staff of academic institutes. This had had a positive impact in subsequent years the number of scientists who had degrees was significantly increased. It was possible to complete the candidates of sciences almost completely in academic institutes and universities. The contingent of scientists with scientific degrees in sectoral research institutes has significantly increased. A study of the scientific potential training system that Ukraine inherited from the Soviet graduate studies found out why the expected progress had not been made during that period. The mastering of new directions of scientific research and practical tasks in terms of breaking close economic and technical connections with the former Soviet Union republics led to the development of postgraduate studies. An analysis of the postgraduate institutes of higher education activities, academic and sectoral research institutes during the 1990s - 2000s has shown that the process of reconstruction has only just begun.
The analysis of the professional training features of the Ukraine scientific potential. The experience and prospects
Keywords: підготовка кадрів вищої кваліфікації; професійна освіта; науковий потенціал; training of highly qualified personnel; professional education; scientific potential